KUALITAS PELAYANAN PEMUNGUTAN PAJAK KENDARAAN BERMOTOR DI UNIT PELAYANAN (UP) PENDAPATAN TAPUNG KABUPATEN KAMPAR - Ikhsan Rochmadi; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Service Quality on community is used as a benchmark in view successful of an organization, then the service functions necessary to be improved to give satisfaction of the taxpayer. In increasing the tax revenue of motor vehicles, policies that is determined by Riau Province manage the local tax namely Revenue Office of Riau Province through regulation of Head of Revenue Office of Riau Province No.05 year 2013 about job description of Revenue Service Unit of Revenue Office of Riau province but it still complaints of taxpayers about the services that exist in the Service Unit Tapung of Kampar Regency, According to this problem, the researcher interested to examined how the service quality of motor vehicle tax collection at Revenue Services Unit Tapung of Kampar regency.Researcher used the theory of Agus Dwiyanto that service quality can be determined by the dimensions of Officer Attitude, Procedures, Time, Facility, Services. This research used descriptive qualitative, data was obtained through interviews that was be submitted to the informant then analyzed by the researcher. And then was collected secondary data relating to the issues that was studied.From this research results show that Revenue Service Unit of Tapung of Kampar Regency is not optimal in service quality, and still under of the expectations of taxpayers, it started from inadequate facilities, lack of certainty of time, it is not include to the good service indicator.Keywords : Service Quality , Revenue Service Unit of Tapung